Effect of Coarse Aggregate Gradation and Water-Cement Ratio on Unit Weight and Compressive Strength of No-fines Concrete - Tunio, Z. A.; Memon, B. A.; Memon, N. A.; Lakho, N. A.; Oad, M.; Buller, A. H. (Engineering, Technology & Applied Science Research, 2019)
Self-weight of a structure comprises a major portion of the overall structural load which causes conservative structure design. Reduction of structures’ self-weight is an active area of research today. One of the options is to use lightweight concrete and no-fines concrete is one of its types. This type of concrete is made with coarse aggregates, cement, and water. From the density point of view, it is the lighter concrete compared to normal weight concrete but it exhibits less strength. Normally no-fines concrete is manufactured with uniform size aggregates. The performance of no-fines concrete depends on the cement-aggregate ratio and water-cement (w/c) ratio. This study focuses on investigating experimentally the effect of gradation of coarse aggregates and the w/c ratio on unit weight and compressive strength of no-fines concrete. NFC with two cement-aggregate ratios (1:6 and 1:8) having seven combinations of coarse aggregate gradations (10-5 mm, 16-13mm, 20-16mm, 20-13mm, 20-10mm, 16-10mm and 20-5mm) were studied. Two w/c ratios are considered 0.38 and 0.42. The effect of coarse aggregate gradation, cement-aggregate ratio and w/c ratio are studied in terms of unit weight and compressive strength of NFC. The results reveal the pronounced effect of aggregate gradation on the compressive strength and unit weight of the concrete. Also, a substantial effect on the unit weight and compressive strength is observed with the variation in cement-aggregate ration and the w/c ratio.